Identification the Causes of Diseases Caused by Fungi and the Intensity of Their Attacks on Shallots (Allium ascalonicum L.) in Bungaraya Village, Bungaraya Sub-district, Siak district - Irfandri; Ali, Muhammad; Khavifah, Alviatul (Talenta Publisher, 2022)
The demand of shallots that increase are not balanced with their productions especially in Riau. One of the main cause of low productivity is the attack of nuisance plant organism. The research aims to analyze the diseases that are caused by fungi and the intensity of their attacks on Shallots in Bungaraya Village, Bungaraya Sub District, Siak Regency. The research is done by using an exploration method; observing the diseases attacks intensity in field and observation; isolation and purification of shallots’ fungi, identification of fungi’ isolate on shallots. The intensity observation of diseases attack in field is done by diagonal method by determining the 5 points of samples randomly, then observing the kind of diseases that are found base on the symptoms and their intensity of attacks. The Identification of disease cause Fungi isolate observed the characteristic of macroscopic and microscopic mushroom. The result shows that the early diagnosis of diseases in the field on shallots in Bungaraya Village, Bungaraya Sub District, Siak Regency is withered fusarium diseases that is caused by A. porri fungi. The attack intensity of withered fusarium diseases is 80,51% and the attack intensity of purple spot diseases is 2,85%